Trademark Counterfeiting: A Legal Review and Its Implications for Consumer Protection - Yeti S Hasan; Sofyan Ratu Ela; Nurlaika Yulifwi; Saskia Musa; Aldy Syaputra Macmud (Indonesian Civil Law Review, 2025)
Trademark counterfeiting is a form of intellectual property rights infringement that has a significant impact on consumer protection. In the Indonesian context, this phenomenon is increasingly prevalent along with the growth of trade and weak legal supervision, which causes consumers to often fall victim to counterfeit products that do not comply with quality, safety, and information standards as they should. This research uses a normative juridical approach by examining related laws and regulations, such as Law Number 20 of 2016 concerning Trademarks and Geographical Indications and Law Number 8 of 1999 concerning Consumer Protection. The results of the study show that trademark counterfeiting not only harms legitimate trademark owners, but also creates legal uncertainty and violations of consumer rights. In addition to impacting economic losses and public health, trademark counterfeiting also erodes public trust in the market system and legal protection. Therefore, integrated efforts are needed in law enforcement, consumer education, and strengthening inter-agency coordination to create an effective and fair consumer protection system.